Plant assisted synthesis of silver nanoparticles using Persicaria perfoliata (L.) for antioxidant, antibacterial, and anticancer properties - Deepak Kumar Shrestha; Dipak Raj Jaishi; Indra Ojha; Dinesh Raj Ojha; Ishwor Pathak; Akash Budha Magar; Niranjan Parajuli; Khaga Raj Sharma (Heliyon)
Persicaria perfoliata (L.) is an herbaceous medicinal plant belonging to the Polygonaceae family. The plant is distributed in Nepal, India, Japan, China, Russia, and Korea. The present study involved the analysis of plant secondary metabolites, synthesis of silver nanoparticles (Ag NPs) using the plant, characterization, and exploration of antioxidant, antidiabetic, antibacterial, and cytotoxic activities. Among six different solvent extracts, the methanol extract displayed the highest total phenolic content (TPC) and total flavonoid content (TFC) of 68.61 ± 0.57 mg GAE/g and 40.69 ± 5.0 mg QE/g respectively. Ag NPs and hexane extract displayed the potential antioxidant activity of IC50 69.40 ± 0.13 and 144.50 ± 1.36 μg/mL in the DPPH assay. The α-amylase inhibition shown by an aqueous extract and the synthesized Ag NPs IC50 of 1188.83 ± 33.52 and 1369.30 ± 46.86 μg/mL respectively. In antibacterial activity, the highest ZOI of 16 mm was displayed by Ag NPs against Klebsiella pneumoniae followed by a ZOI of 11 mm for methanol extract against Shigella sonnei. Similarly, the lowest MIC and MBC of 0.78125 and 1.5625 mg/mL were recorded for both Ag NPs and methanol extract against Staphylococcus aureus. Aqueous extract and Ag NPs did not display significant toxicity against brine shrimp nauplii. Ag NPs displayed an IC50 of 251.86 ± 58.90 μg/mL against HeLa cell lines. Biosynthesized Ag NPs showed a distinct peak at 409 nm in UV–visible spectra. FTIR analysis revealed the involvement of different functional groups of the organic compounds present in plant extract as reducing, capping, and stabilizing agents in the synthesis of Ag NPs. XRD analysis confirmed the crystal structure of Ag NPs, whereas the average grain size of 44.28 nm was determined by FE-SEM analysis. EDX spectra established the elemental composition of Ag NPs. The present study shows the synthesized Ag NPs using plant extract impart the potential biological activities as compared to that of the crude extract.